Genome-wide analysis reveals TNFAIP8L2 as an immune checkpoint regulator of inflammation and metabolism. (July 2018) - Li, Ting; Wang, Wei; Gong, Shunyou; Sun, Honghong; Zhang, Huqin; Yang, An-Gang; Chen, Youhai H.; Li, Xinyuan
Highlights: TNFAIP8L2 was preferentially expressed in human myeloid cell types. Tnfaip8l2 expression drastically decreased after lipopolysaccharide treatment in macrophages. Tnfaip8l2 deficiency led to heightened gene expression enriched for leukocyte activation and lipid biosynthesis pathways. Tnfaip8l2 negatively regulated mitochondrial respiration in response to lipopolysaccharide. Hyperlipidemia condition upregulated Tnfaip8l2 gene expression in the adipose tissue. Abstract: The interplay between inflammation and metabolism is widely recognized, yet the underlying molecular mechanisms remain poorly characterized. Using experimental database mining and genome-wide gene expression profiling methods, we found that in contrast to other TNFAIP8 family members, TNFAIP8L2 (TIPE2) was preferentially expressed in human myeloid cell types. In addition, Tnfaip8l2 expression drastically decreased in lipopolysaccharide (LPS)-stimulated macrophages. Consequently, Tnfaip8l2 deficiency led to heightened expression of genes that were enriched for leukocyte activation and lipid biosynthesis pathways. Furthermore, mitochondrial respiration rate was increased in Tnfaip8l2-deficient macrophages, as measured by Seahorse metabolic analyzer. Taken together, these results indicate that Tnfaip8l2 serves as a "brake" for immunometabolism, which needs to be released for optimized metabolic reprogramming as well as mounting effective inflammatory responses. The unique anti-inflammatory and metabolic-modulatory function of TNFAIP8L2 renders it a novel therapeutic target for cardiovascular diseases and cancer.